Counseling Religious for Character Building - Aslamiah; Safitri, Syiva; Alfiansyah, Sendi; Rahman, Siti Muthia (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Islamic religious education is a subject that has the responsibility to shape the character of students in fact, the task of forming character lies with all teachers and especially parants. Guidance counseling services at school are a forum for students to convoy their complaints and problems. This research aims to develop a counsling -based model of Islamic religious education to build the character of students which is packaged in the form of a consul card. The method used in this research is the research and development method from Borg & Gall using 10 stages. Feasibility of an expert model. The subjects in this research were students in clases VIII 1 and VIII 6 Junior High School 19, Bekasi City, while the object of the research was the students character values. This research begins with collacting planning information. Development of product forms, expert validation, revision, and small group trials. The research results show that the counseling-based model of Islamic religious education must always be developed in the context of innovation in Islamic religious education in responding to students' needs, counseling will be more effective, interesting and meaningful by using counseling based on Islamic religious education, and this model can be used as an alternative to various models. counseling.